Penggunaan Metode Diskusi terhadap Keteramplan Menulis Teks Ulasan - Hendrisman Hendrisman (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2019)
The purpose of this study was to describe the effect of the use of the discussion method on the writing skills of the eighth grade students' MTsN Dangung-Dangung District Five Puluh City. The method used is an experimental method. The results of the study found that learning by the discussion method affected the writing skills of the eighth grade students of MTsN Dangung-Dangung, Lima Puluh Kota. Data analysis shows that the discussion method has an effect on the skills of writing review texts. This is evidenced by an increase in the experimental class with the student score pretest time mean value ( ) is 67 after the discussion method has been applied, an increase with an average value / mean ( ) is 83. Whereas in using conventional methods students also value effect even if the increase in value is not too high. The pretest time mean value ( ) is 48. After applying conventional methods, the average value increase (mean) is 61. So the learning outcomes of students taught using the discussion method are better than the learning outcomes of students in the control class taught with conventional learning. Keywords: Discussion Method, Writing Review Texts.